In vivo self-incompatibility response in the wild potato Solanum chacoense bitter - Capurro, Mauricio Antonio (2012)
In tuber-bearing Solanum species (potatoes), S-locus mediated self-incompatibility is under gametophytic control. In this system, self-fertilization is avoided when the same S-allele is expressed in both pistil and pollen. Because the ultrastructural details of the self-incompatibility response in this group of species is unknown, the aim of this study was to identify the cellular events involved in this response by using the diploid species S. chacoense Bitter as a model. To this end, pollinations were carried out in two genotypic combinations previously identified as (1) compatible and (2) self-incompatible (self-pollination) for the S-locus. Pollinated pistils were fixed on an hourly basis and observed under a transmission electron microscope to detect ultrastructural changes. In the self-incompatible genotypic combination, pollen grains germinated normally but loss of electron density in the mitochondrial matrix of pollen tubes was observed at 1 hour after pollination (HAP), mitochondrial swelling started at 2 HAP and, finally, mitochondrial content was lost at 7 HAP, with the concomitant cessation of pollen tube growth in the upper third of the style. The gametophytic self-incompatibility response in potato shares similarities with a type of programmed cell death.